Familiar violence: explanatory models of the process through case study - Miljánovich Castilla, Manuel (2013)
According to working hypothesis from this further research, the aggressor behavior predisposed factors (husband or partner),this is, his tendency to exert physical and psychological violence against his partner and children, It’s originated in a violent environment in which the aggressor developed his childhood associated to lack of affection and material things. The same type of predisposed factors, also influences in the perceptions and interpretations of the attacked woman, in respect of the familiar violence, in what she and her children are victims.